Field Testing and Analysis of Embankment Vibrations Induced by Heavy Haul Trains - Peng Li; Xianzhang Ling; Feng Zhang; Yan Li; Yingying Zhao (Shock and Vibration)
This paper presents a field testing of track and ground-borne vibration generated by heavy haul trains. The test sites consisted of three embankments with height of 6.6, 8.1, and 11.9, respectively. The acceleration signals of the rail, sleeper, and embankment surface were recorded, and then the propagation characteristics of ground vibration with distance to track center were contrastively analyzed. The test results show that horizontal vibration was dominant for locations near the track but decreased rapidly and became comparable with the vertical levels as the distance from track center increases. The quasi-static excitation dominated the sleeper response, and the dominant frequency range was found in the low-frequency zone corresponding to the fundamental axle passage frequency. For embankment surface, another pronounced dominant frequency zone was observed between 30 and 80 Hz, which was attributed to the dynamic excitation. Moreover, these higher frequency components were more promptly attenuated than low-frequency ones. The reason that vibration levels generated by locomotive were greater than wagon was attributed to the different bogie suspension mode. The relationship between normalized PPV and distance from track center in doubly logarithmic scales can be expressed with exponential function, and the vibration attenuation rates were restrained with increasing the embankment height.